The comparison of clinical outcomes between volar locking plate fixation and dual-plate fixation in high-energy distal radius fractures - Zhou, Lingyao; Gao, Yuling; Wang, Dong; Zhao, Yanrui; Lu, Tianchao; Wang, Hanzhou; Zhao, Binzhi; Guo, Jianwei; Li, Ziyi; Liu, Yang; Zhou, Junlin (Frontiers in Surgery, 2025)
PurposesThe aim of this study was to compare clinical outcomes of dual-plate fixation and volar locking plate fixation in high-energy intra-articular distal radius fractures.MethodsIn this study, 168 patients with high-energy intra-articular distal radius fractures with either volar fragments, dorsal fragments, or radial styloid fragments, who were treated with one of three kinds of fixation methods (volar locking plate fixation, volar + radial plating fixation, and dorsal + radial plating fixation) were retrospectively reviewed and divided into three groups. Functional evaluations included DASH score, Mayo wrist score, wrist joint ROM, and grip strength percentage relative to the healthy side. Radiographic parameters assessed were volar tilt, radial inclination, radial height, and ulnar gap/step distance. Any complications were documented.ResultsSignificant differences were found in volar tilt, radial inclination, and gap/step distance 1 month postoperatively between the volar locking plate fixation group, the volar + radial plating group, and the dorsal + radial plating group. And the volar + radial plating group showed significant difference from the dorsal + radial plating group for the gap/step distance 1 month postoperatively (p < 0.01). Forty-six complications were recorded for 15 cases of the volar locking plate fixation group, 16 cases of the volar + radial plating group, and 15 cases of the dorsal + radial plating group.ConclusionsFor high-energy distal radius fractures, volar locking plate fixation and dual-plate fixation achieved similarly positive functional and radiological outcomes. The dual-plate fixation method has the advantage of achieving better reduction quality.